COLUMN AND BATCH REGENERATION STUDIES FOR ZINC REMOVAL ON DIFFERENT ANIONIC EXCHANGE RESINS - GÎLCĂ, Emilia; MĂICĂNEANU, Andrada; ILEA, Petru (Studia Universitatis Babeș-Bolyai Chemia, 2015)
Five anion exchange resins were used to remove zinc chloride complexes from a synthetic acid pickling bath. The experiments were carried out for several cycles of adsorption-desorption in fixed bed column and batch mode. The results showed that the percent of zinc chloride sorption remained constant in the last three cycles (from six) in both cases. Comparing various resins, the following series was depicted based on the ionic exchange capacity: Purolite A600MB > Amberlite IRA410 > Purolite A103S > Purolite A400MBOH > Purolite NRW700. Also, it was possible to concentrate the metal in smaller solution volume after regeneration, which will make its recovery much easier.